A percepção das famílias acerca da inclusão escolar de seus filhos com altas habilidades/superdotação - Rigon, Rafaela Camila (My University, 2024)
This dissertation is linked to the Educational Processes, Language, Technology and Inclusion line and investigates the inclusion of students with High Abilities/Giftedness (AH/SD) from the perspective of families. The research aims to understand how the families of students with High Abilities/Giftedness perceive and reorganize themselves for the school inclusion of their children. The understanding of AH/SD is taken from Renzulli (1998; 2004; 2014; 2021) with the Three Ring Theory and the recognition of human capabilities, considering the family context, school and other social spaces. The discussion about in/exclusion present in the school process is carried out based on Lopes, Hattage and Lockmann (2012) and Lopes (2007; 2011; 2013). Gallo (2009; 2016; 2019; 2021) helped with discussions about difference and inclusion. This is a qualitative and exploratory study, using semi-structured interviews to construct the data. Eight mothers participated who reported their experiences in the process of identifying and educating their children. The narratives were analyzed based on content analysis by Bardin (2021), two categories emerging: "It's so cool that you can talk to people who understand you" and "Before identification, she was happy". The results highlight the loneliness of mothers on the journey with their children and the in/exclusion movements of students at school. It Is concluded that mothers actively participate in the process of identifying their children and in the process of identifying their children, some mothers identified themselves. Welcoming is essential for the child to feel included in the learning process and in the school environment, as myths and lack of knowledge on the subject make the process of identification and socialization difficult. [resumo fornecido pelo autor]
Esta dissertação está vinculada à linha Processos Educacionais, Linguagem, Tecnologia e Inclusão e investiga a inclusão de alunos com Altas Habilidades/Superdotação (AH/SD) a partir da perspectiva das famílias. A pesquisa tem o objetivo de compreender como as famílias dos alunos com Altas Habilidades/Superdotação percebem e se reorganizam para a inclusão escolar de seus filhos. A compreensão de AH/SD é tomada a partir de Renzulli (1998; 2004; 2014; 2021) com a Teoria Dos Três Anéis e do reconhecimento das capacidades humanas, considerando o contexto familiar, a escola e os demais espaços sociais. A discussão sobre in/exclusão presente no processo escolar é realizada a partir de Lopes, Hattage e Lockmann (2012) e Lopes (2011; 2007; 2013). Gallo (2009; 2016; 2019; 2021) auxiliou nas discussões sobre diferença e inclusão. Este é estudo qualitativo e exploratório, contou com entrevistas semi-estruturadas para a construção dos dados. Participaram 8 mães que relataram suas experiências no processo de identificação e escolarização de seus filhos. As narrativas foram analisadas a partir da análise de conteúdo de Bardin (2021), emergindo duas categorias: "É tão legal tu falar isso com pessoas que te entendem" e "Antes da identificação era feliz". Os resultados evidenciam a solidão das mães no percurso com seus filhos e os movimentos de in/exclusão dos alunos na escola. Conclui-se que o acolhimento é essencial para que a criança se sinta inserida no processo de aprendizagem e no meio escolar, sendo que os mitos e falta de conhecimento sobre a temática dificultam o processo de identificação e a socialização. [resumo fornecido pelo autor]
Keywords: Superdotados - Educação; Família; Inclusão escolar; Prática de ensino; Educação; Gifted persons - Education; Family; Mainstreaming in education; Student teaching; Education